(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Lack of access to safe, timely, affordable and respectful abortion is a critical public health and human rights issue. Abortion till date has been unique debated problem in the field of biomedical consciences. Ethnopharmacological data reveals that plant Plumeria acuminata, of the Apocynaceae family, has exhibited several activities like anti-fertility, anti-pyretic, anti-nociceptive, anti-bacterial, anti-diabetic, anti-tumour, and immune-modulatory as well as abortifacient activities. As per our knowledge, no exploratory studies have been conducted to discover the actual abortifacient potential of this plant till to date. For this purpose, the aim of this study was to evaluate the biological activity of P. acuminata leaves and roots ethanolic extracts with respect to their effects in hormonal and histological regulations, eventually leading to abortion. Ethanolic extracts of harvested P. acuminata leaves and roots were prepared through a cold maceration process, subjected to qualitative phytochemical analysis and acute toxicity test. Based on the LD50 values, 100, 200, and 400 mg/kg doses of both extracts were determined for abortifacient activity in mated adult Wistar female rats. Misoprostol was administered at 0.1 mg/kg, p.o, as a standard abortion-inducing drug. Standard and test-item treatments were given from gestation day (GD) 7 to 14. Morphological, hematological, hormonal, and histological examinations were performed on GD20 after euthanizing animals. Administration of extracts significantly altered the hormonal levels up to 20-30% i.e., decrease in estrogen and progesterone as well as increased PGE-1 and acetylcholine. Anatomical alterations in reproductive organs were confirmed by observing cystic follicles and atrophied squamous cells during histopathological evaluation. Visual observations of uterine horns confirmed 25% live fetus, 28% early resorption, 30% late resorption resulting in 75% post-implantation loss. Obtained abortifacient results can be attributed to the presence of plumericin, sterol and lupeol triterpene groups of phytochemicals present in leaves and roots ethanolic extracts, making them a potent candidate for natural abortifacient medicines.